The coastal marind language - Olsson, Bruno (2018)
This thesis is a descriptive grammar of Coastal Marind, an Anim language of Southern New Guinea. The description of the language is based on 8 hours of transcribed video recordings collected during ca. 13 months of field research in Merauke (Indonesia) and in nearby Marind-speaking villages. The thesis describes phonology (Chapter 2), word classes (Chapter 3), nominals (Chapters 4-6), various categories associated with the verb (Chapters 7-15), basic syntax (Chapter 16) and non-affirmative speech acts (Chapter 17). Some of the descriptively and theoretically most challenging issues in Coastal Marind are its complex verb morphology and the structure of the verb, the gender system, and an unusual system of focus marking on the verb ('Verb Orientation'), all of which are described in detail.